Obstacles in The Implementation of Sayang Bunda E-Health Application - Ambar Dwi Erawati; Chusnul Zulaika; Mona Tiorina Manurung (Journal of Educational, Health and Community Psychology, 2021)
Background: The Sayang Bunda application is an E-Health android application offered by the Semarang City Health Office which provides consultation services to pregnant women and postpartum mothers. E-Health is considered effective as a medium for consulting pregnant women in the city of Semarang. However, based on a preliminary survey to pregnant women, there are pregnant women who do not use and even do not know the application. The purpose of this study was to explore the obstacles in the implementation of the "Sayang Bunda" E-Health Application. Research Methods: This research is a qualitative research where this research is basic and aims to obtain information and data related to the implementation of the Sayang Bunda E-Health application. Data collection techniques use interviews with the health center coordinator midwives and questionnaires with pregnant women and postpartum mothers. The subjects of this study are pregnant women, postpartum mothers, and the managers of community health centers. The study results show that pregnant women and postpartum mothers prefer WhatsApp groups to have consultation related to pregnancy, childbirth, postpartum and newborns since it is easier to do. It is recommended to have policy integration among several parties so that the implementation of the Sayang Bunda E-Health can be carried out optimally.Â Keywords: E-Health, Obstacles, Implementation.Â